CHI '05 Extended Abstracts on Human Factors in Computing Systems 2005
DOI: 10.1145/1056808.1056975
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic semantics for natural language interfaces

Abstract: An important way of making interfaces usable by nonexpert users is to enable the use of natural language input, as in natural language query interfaces to databases, or MUDs and MOOs. When the subject matter is about procedures, however, we have discovered that interfaces can take advantage of what we call Programmatic Semantics, procedural relations that can be inferred from the linguistic structure. Roughly, nouns can be interpreted as data structures; verbs are functions; adjectives are properties. Some lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Revision of hundreds of steps is a difficult and time-consuming task. Therefore, there are recent researches that focus on detecting user intent from natural languages [37] Lau [38] propose the Co-Tester system suggesting a new language called ClearScript. The tester should provide the cotester system with segmented test steps so that the system can handle them.…”
Section: Fig 4 Hybrid Testing Frameworkmentioning
confidence: 99%
“…Revision of hundreds of steps is a difficult and time-consuming task. Therefore, there are recent researches that focus on detecting user intent from natural languages [37] Lau [38] propose the Co-Tester system suggesting a new language called ClearScript. The tester should provide the cotester system with segmented test steps so that the system can handle them.…”
Section: Fig 4 Hybrid Testing Frameworkmentioning
confidence: 99%
“…However, the programmer's thinking must already be precise enough to know almost exactly what should happen at each line. Metafor [Liu and Lieberman 2005] and its successor MOOIDE [Lieberman and Ahmad 2010] use sentence structure and mixed-initiative discourse to understand compound descriptions. MOOIDE further showed that general background world knowledge helps to understand natural language input.…”
Section: Programming In Natural Languagementioning
confidence: 99%
“…Natural language definitions of protocol semantics are intuitive, but they are inherent ambiguities. By using programmatic semantics [13] together with animations, representational flexibility of different protocol demonstration is retained for as long as it is needed.…”
Section: Natural Language Protocol Specifications (Nlps)mentioning
confidence: 99%